2010
DOI: 10.1038/modpathol.2009.164
|View full text |Cite
|
Sign up to set email alerts
|

Most primary central nervous system diffuse large B-cell lymphomas occurring in immunocompetent individuals belong to the nongerminal center subtype: a retrospective analysis of 31 cases

Abstract: Primary central nervous system lymphomas are rare neoplasms characterized by a dismal prognosis relative to other extranodal lymphomas. Approximately 98% of primary central nervous system lymphomas are of B-cell origin, and most belong to the diffuse large B-cell type. Recently, diffuse large B-cell lymphomas have been subcategorized into germinal center and nongerminal center types based on gene expression profiles and immunohistochemical expression of CD10, Bcl-6, and MUM1. Studies have shown that the overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
41
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 24 publications
(26 reference statements)
11
41
0
Order By: Relevance
“…b 89 year old female with swelling exhibiting a small ulceration on the surface in the right maxillary vestibule presented with discomfort in denture wearing. (Case #12 Table 3) has been reported in non-GCB DLBCLs in many diverse locations such as the central nervous system, gastrointestinal tract, breast, testes, among others [7,13,32,[35][36][37]47] Our results appear to indicate a similar trend. A significant proportion ([50%) of the patients with non-GCB DLBCL succumbed to their disease, though limited information was available on the treatment these patients underwent.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…b 89 year old female with swelling exhibiting a small ulceration on the surface in the right maxillary vestibule presented with discomfort in denture wearing. (Case #12 Table 3) has been reported in non-GCB DLBCLs in many diverse locations such as the central nervous system, gastrointestinal tract, breast, testes, among others [7,13,32,[35][36][37]47] Our results appear to indicate a similar trend. A significant proportion ([50%) of the patients with non-GCB DLBCL succumbed to their disease, though limited information was available on the treatment these patients underwent.…”
Section: Discussionsupporting
confidence: 88%
“…Similar studies analyzing GCB and non-GCB subgroups of DLBCL have been conducted in tumors of the breast [36], CNS [47] and testes [35] and have revealed that non-GCB tumors exhibit a high proliferative rate and poor prognosis compared to GCB lesions. Our study of 13 primary DLBCLs shows that non-GCB lesions predominate and may exhibit a poorer prognosis with half of the patients succumbing to their disease while majority of the GCB group continue to be disease free.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, it was revealed that, unlike systemic DLBCLs, the majority of PCNSLs originate from post-GC, with a low expression of the GC marker CD10, expression of the GC marker BCL-6 and high expression of the activated B cell-like marker MUM-1, which is consistent with the majority of previous studies (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)28,29) (Table III). In addition, the co-expression of BCL-6 and MUM-1 and the absence of late post-GC marker CD138 expression indicated the activated immunophenotype and the early post-GC origin of PCNSL, which was in accordance with Camilleri-Broёt et al (24).…”
Section: Discussionsupporting
confidence: 80%
“…Patients in the GCB subgroup showed an improved prognosis compared with ABC (activated B cell-like; including activated GCB and activated non-GCB, according to Chang's classification) (9,10,12,13). In PCNSL, numerous studies have been performed to observe the prognostic significance of the variable biological markers widely used in systemic DLBCL (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The present study aimed to analyze the expression profile of immunohistochemical Immunohistochemical profile and prognostic significance in primary central nervous system lymphoma: Analysis of 89 cases markers and their potential prognostic significance in 89 Chinese PCNSL cases.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 However, several other studies did not reveal significant survival difference between these two groups. [9][10][11][12] These studies had either a limited total number of patients or very few patients in the GCB group.…”
Section: Introductionmentioning
confidence: 99%